Fuel cell graphite metal composite bipolar plate and preparation method thereof

By adding metal powder to the powder and adopting a multi-step process, graphite metal composite bipolar plates are prepared, which solves the problems of deviation in conductivity and large contact resistance of existing bipolar plates, and achieves efficient conductivity and corrosion resistance.

CN119852434AActive Publication Date: 2025-04-18SHENZHEN SENERGY FUEL CELL TECH CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510198366.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-22
Publication Date
2025-04-18
Estimated Expiration
2045-02-22

AI Technical Summary

Technical Problem

The existing fuel cell bipolar plates have poor conductivity and large contact resistance, which are difficult to meet the actual use needs.

Method used

Graphite metal composite bipolar plate is prepared by adding metal powder to the powder and using heating and pressurization, multi-step solution treatment and metal plating processes to improve its conductivity and corrosion resistance.

Benefits of technology

It achieves low contact resistance, good conductivity and high corrosion resistance of the bipolar plate, which can meet the needs of fuel cells.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a fuel cell graphite metal composite bipolar plate and a preparation method thereof, and the method comprises the following steps: S01, heating and pressurizing mixed powder to obtain a molded composite polar plate; s02, soaking the molded composite polar plate in a first solution at 60-70 DEG C, taking out the molded composite polar plate, and cleaning the molded composite polar plate until the molded composite polar plate is neutral to obtain a pretreated composite polar plate; soaking the pretreated composite polar plate in a second solution at 70-80 DEG C, taking out the pretreated composite polar plate, and washing the pretreated composite polar plate with water to obtain a treated composite polar plate; s03, soaking the treated composite polar plate in a third solution, taking out the treated composite polar plate, washing the treated composite polar plate with water, and activating and washing the treated composite polar plate in an activation solution to obtain an activated polar plate; and S04, placing the activated polar plate in a plating solution for metal plating treatment, and then washing and drying to obtain the fuel cell graphite metal composite bipolar plate. The preparation method is simple, low in production cost, easy to implement and high in production efficiency, and can be used for large-scale production of the bipolar plate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of fuel cells, and in particular relates to a fuel cell graphite metal composite bipolar plate and a preparation method thereof. Background Art

[0002] The bipolar plate (BP) of a fuel cell, also known as the flow field plate, is the "skeleton" of the fuel cell stack. It is assembled with the membrane electrode layer to form a fuel cell stack. It plays the role of supporting, collecting current, providing channels for coolant, and separating oxidants and reductants in the fuel cell.

[0003] At present, the common bipolar plates mainly include graphite plates, metal plates and composite bipolar plates. Among them, graphite plates have the advantages of excellent conductivity and corrosion resistance, but they are not easy to make thin and are prone to breakage; while metal plates have the advantages of excellent conductivity, high strength and thinness, but due to the harsh environment inside the battery stack, metal plates are prone to corrosion.

[0004] To solve the above contradiction, the composite bipolar plate combines the advantages of both to achieve thinner plates while maintaining good corrosion resistance. Existing composite plates are mainly composite plates made of graphite and resin. In order to ensure strength, an appropriate amount of resin is added to them. However, the resin is a non-conductor, which leads to the overall conductivity deviation of the composite plate and a large contact resistance, which is difficult to meet the needs of actual production and use. Summary of the invention

[0005] The embodiment of the present invention provides a fuel cell graphite metal composite bipolar plate and a preparation method thereof, aiming to solve technical problems such as deviation in conductivity performance, large contact resistance, and difficulty in meeting actual use requirements of existing bipolar plates.

[0006] In order to solve the above technical problems, on the one hand, an embodiment of the present invention provides a method for preparing a fuel cell graphite metal composite bipolar plate, comprising the following steps:

[0007] S01, heating and pressurizing the mixed powder to obtain a formed composite plate; the heating temperature is 280°C to 400°C; the pressurizing pressure is 15MPa to 25MPa, and the pressurizing time is 10min to 20min;

[0008] S02, soaking the formed composite plate in a first solution at 60°C to 70°C, taking it out, and washing it to neutrality to obtain a pretreated composite plate; soaking the pretreated composite plate in a second solution at 70°C to 80°C, taking it out, and washing it with water to obtain a treated composite plate;

[0009] S03, soaking the treated composite plate in a third solution, taking it out, washing it with water, and then placing it in an activation solution for activation, washing it with water, to obtain an activated plate;

[0010] S04, placing the activated electrode plate in a plating solution for metal plating, then washing with water, and drying to obtain a fuel cell graphite metal composite bipolar plate (graphite metal composite electrode plate with metal plated on the surface).

[0011] As a preferred embodiment, in step S01,

[0012] The mixed powder is prepared by the following method: the powder body and the resin are evenly dispersed to obtain the mixed powder; the mass ratio of the resin to the powder body is 1:4 to 1:6.

[0013] The powder body is prepared by the following method: taking the mass of the powder body as 100%, 60% to 80% of graphite powder, 0.5% to 5% of carbon fiber and 20% to 40% of metal powder are uniformly mixed to obtain the powder body.

[0014] The mixing is carried out in a mixing device; the mixing rotation speed is 600 rpm to 800 rpm, and the mixing time is 30 min to 40 min.

[0015] The resin is a thermoplastic resin.

[0016] The thermoplastic resin is preferably one of polystyrene, polyetheretherketone or polyamide.

[0017] The dispersing rotation speed is 600 rpm to 800 rpm, and the dispersing time is 40 min to 60 min. During the dispersing period, the temperatures of the powder body and the resin are both less than 50°C.

[0018] As a preferred embodiment, in step S02,

[0019] The first solution is a 5 g / L to 10 g / L sodium hydroxide solution. The oil stains on the surface of the plate can be removed by soaking in the first solution.

[0020] The second solution is a mixed solution containing phosphoric acid and chromic acid, the concentration of the phosphoric acid is 200 g / L to 300 g / L, and the concentration of the chromic acid is 100 g / L to 200 g / L.

[0021] As a preferred embodiment, in step S03,

[0022] The third solution is a mixed solution of stannous chloride and hydrochloric acid; the concentration of the stannous chloride is 15g / L-20g / L, the amount of concentrated hydrochloric acid added is 30-40ml / L, and the hydrochloric acid is 37% by mass (12mol / L).

[0023] The soaking temperature is 25° C. and the soaking time is 8 to 10 minutes.

[0024] The activation solution is a mixed solution of palladium chloride and hydrochloric acid; the concentration of the palladium chloride is 0.3g / L to 0.5g / L, and the concentration of the hydrochloric acid is 20ml / L to 30ml / L.

[0025] The activation time is 3 min to 5 min.

[0026] As a preferred implementation, in step S04,

[0027] The plating solution contains 20g / L to 30g / L nickel sulfate, 20g / L to 30g / L sodium hypophosphite, 10g / L to 15g / L sodium acetate and 10g / L to 15g / L sodium citrate.

[0028] The metal plating treatment is carried out during stirring; the stirring speed is 80 rpm to 100 rpm; and the metal plating treatment time is 40 min to 60 min.

[0029] On the other hand, an embodiment of the present application further provides a fuel cell graphite metal composite bipolar plate, wherein the fuel cell graphite metal composite bipolar plate is prepared by the above-mentioned preparation method.

[0030] Compared with the prior art, the technical solution of the embodiment of the present invention has the following beneficial effects: by adding metal powder to the powder material, the present application can reduce the influence of the resin on the conductivity of the bipolar plate while effectively improving the conductivity of the composite powder; by adding a surface treatment process to the bipolar plate, not only the conductivity of the bipolar plate is further improved, but also the corrosion resistance of the bipolar plate is effectively enhanced. The preparation method of the present application is simple, low in production cost, easy to implement, greatly shortens the preparation cycle of the plate, has high production efficiency, and can be used for large-scale production of bipolar plates. The prepared fuel cell graphite metal composite bipolar plate has low contact resistance, high molding efficiency, good performance, and can meet the use needs of fuel cells. DETAILED DESCRIPTION

[0031] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the fact that ordinary technicians in the field can implement it. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such combination of technical solutions does not exist and is not within the scope of protection required by the present invention.

[0033] At present, the existing bipolar plates have problems such as conductivity deviation, large contact resistance, and difficulty in meeting the actual use needs. In order to solve the above technical problems, an embodiment of the present invention provides a method for preparing a fuel cell graphite metal composite bipolar plate, comprising the following steps:

[0034] S01, heating and pressurizing the mixed powder to obtain a formed composite plate; the heating temperature is 280°C to 400°C; the pressurizing pressure is 15MPa to 25MPa, and the pressurizing time is 10min to 20min;

[0035] S02, soaking the formed composite plate in a first solution at 60°C to 70°C, taking it out, and washing it to neutrality to obtain a pretreated composite plate; soaking the pretreated composite plate in a second solution at 70°C to 80°C, taking it out, and washing it with water to obtain a treated composite plate;

[0036] S03, soaking the treated composite plate in a third solution, taking it out, washing it with water, and then placing it in an activation solution for activation, washing it with water, to obtain an activated plate;

[0037] S04, placing the activated electrode plate in a plating solution for metal plating, then washing with water, and drying to obtain a fuel cell graphite metal composite bipolar plate (graphite metal composite electrode plate with metal plated on the surface).

[0038] As a preferred embodiment, in step S01,

[0039] The mixed powder is prepared by the following method: the powder body and the resin are evenly dispersed to obtain the mixed powder; the mass ratio of the resin to the powder body is 1:4 to 1:6. By controlling the dosage ratio of the powder body and the resin, the obtained plate has good hardness, and while effectively improving the conductivity of the composite powder, the influence of the resin on the conductivity of the bipolar plate can be reduced. If the amount of resin is too high, the conductivity of the obtained bipolar plate is poor; if the amount of resin is too low, the strength of the plate cannot be guaranteed.

[0040] The powder body is prepared by the following method: taking the mass of the powder body as 100%, 60% to 80% of graphite powder, 0.5% to 5% of carbon fiber and 20% to 40% of metal powder are uniformly mixed to obtain the powder body. By controlling the usage ratio of graphite powder, carbon fiber and metal powder, the conductivity of the powder body can be effectively improved while reducing the influence of the resin on the conductivity of the bipolar plate.

[0041] The graphite powder is preferably natural graphite powder, artificial graphite powder (such as isostatically pressed graphite powder) or flexible graphite powder.

[0042] The particle size of the natural graphite powder is 10 μm to 50 μm; the particle size of the artificial graphite powder is 15 μm to 45 μm; and the particle size of the flexible graphite powder is 20 μm to 40 μm.

[0043] The carbon fiber has a length of 0.1 mm to 10 mm and a diameter of 5 μm to 10 μm.

[0044] The metal powder is preferably one of stainless steel powder, titanium powder, aluminum powder or copper powder.

[0045] The particle size of the stainless steel powder is 25 μm to 75 μm; the particle size of the titanium powder is 30 μm to 90 μm; the particle size of the aluminum powder is 15 μm to 60 μm; and the particle size of the copper powder is 10 μm to 50 μm.

[0046] The mixing is carried out in a mixing device; the mixing speed is 600 rpm to 800 rpm, and the mixing time is 30 min to 40 min. In this way, the powder can be fully mixed.

[0047] The resin is a thermoplastic resin.

[0048] The thermoplastic resin is preferably one of polystyrene, polyetheretherketone or polyamide.

[0049] The dispersing speed is 600 rpm to 800 rpm, and the dispersing time is 40 min to 60 min. During the dispersing period, the temperature of the powder body and the resin is less than 50° C. In this way, it is possible to effectively prevent the powder and the resin from being overheated and affecting the state of the resin and the powder, thereby affecting the mixing effect.

[0050] As a preferred embodiment, in step S02,

[0051] The first solution is a 5 g / L to 10 g / L sodium hydroxide solution. The oil stains on the surface of the plate can be removed by soaking in the first solution.

[0052] The soaking time is 10 to 15 minutes.

[0053] The cleaning is performed by washing with deionized water.

[0054] The second solution is a mixed solution containing phosphoric acid and chromic acid, the concentration of the phosphoric acid is 200g / L to 300g / L, and the concentration of the chromic acid is 100g / L to 200g / L. By adding the first solution and the second solution to the bipolar plate, the conductivity of the bipolar plate is further improved, and the corrosion resistance of the bipolar plate is effectively enhanced.

[0055] The water washing is performed by using deionized water.

[0056] In the embodiment of the present application, the immersion temperature of the second solution is higher than that of the first solution, so that the surface of the electrode plate can be better treated, so that it can be better sensitized and activated, which is conducive to the formation of palladium particles on the surface of the electrode plate.

[0057] As a preferred embodiment, in step S03,

[0058] The third solution is a mixed solution of stannous chloride and hydrochloric acid; the concentration of the stannous chloride is 15g / L-20g / L, the amount of concentrated hydrochloric acid added is 30-40ml / L, and the hydrochloric acid is 37% by mass (12mol / L).

[0059] The immersion temperature is 25°C and the immersion time is 8 to 10 minutes. By immersing, the plate can be sensitized so that the surface of the plate adsorbs tin ions (Sn 2+ ).

[0060] The activation solution is a mixed solution of palladium chloride and hydrochloric acid; the concentration of the palladium chloride is 0.3g / L to 0.5g / L, and the concentration of the hydrochloric acid is 20ml / L to 30ml / L.

[0061] The activation time is 3 to 5 minutes. Through the activation treatment, palladium particles can be formed on the surface of the plate, and the palladium particles can serve as the catalytic center of the plate.

[0062] As a preferred implementation, in step S04,

[0063] The plating solution contains 20g / L to 30g / L nickel sulfate (NiSO4), 20g / L to 30g / L sodium hypophosphite (NaH2PO2), 10g / L to 15g / L sodium acetate (CH3COONa) and 10g / L to 15g / L sodium citrate (C6H5Na3O7).

[0064] In the embodiment of the present application, the composition of the plating solution can be adjusted according to actual needs, and can also be replaced with a copper plating solution for copper plating. The conductive performance of the electrode plate can be further improved by plating solution treatment.

[0065] The pH value of the plating solution is 4.5-5.0; the pH value is adjusted by acetic acid or sodium hydroxide.

[0066] The temperature of the plating solution is 80°C to 90°C. By controlling the temperature of the plating solution, the quality of the coating can be effectively guaranteed. Too low a temperature will result in a slow deposition rate of the coating and the appearance of pores; too high a temperature will increase the stress of the coating, making it easy to become brittle and crack, and the reaction rate will be too fast and difficult to control.

[0067] The metal plating process is carried out during stirring; the stirring speed is 80 rpm to 100 rpm; the metal plating process lasts for 40 min to 60 min. In this way, the uniformity of the plating solution can be ensured, so that the surface consistency of the plate is high, thereby ensuring the stability of the plate performance.

[0068] The water washing is performed by cleaning with deionized water.

[0069] The drying temperature is 100°C to 120°C.

[0070] In the embodiments of the present application, the solution of the present application can be implemented as long as the operating conditions are controlled within the above parameter range.

[0071] Example 1

[0072] A method for preparing a fuel cell graphite metal composite bipolar plate comprises the following steps:

[0073] S01, heating and pressurizing the mixed powder to obtain a formed composite plate; the heating temperature is 370° C.; the pressurizing pressure is 25 MPa, and the pressurizing time is 15 min;

[0074] S02, soaking the formed composite plate in a first solution at 70° C., taking it out, and washing it to neutrality to obtain a pretreated composite plate; soaking the pretreated composite plate in a second solution at 75° C., taking it out, and washing it with water to obtain a treated composite plate;

[0075] S03, soaking the treated composite plate in a third solution, taking it out, washing it with water, and then placing it in an activation solution for activation, washing it with water, to obtain an activated plate;

[0076] S04, placing the activated electrode plate in a plating solution for metal plating, then washing with water, and drying to obtain a fuel cell graphite metal composite bipolar plate (graphite metal composite electrode plate with metal plated on the surface).

[0077] In step S01,

[0078] The mixed powder is prepared by the following method: 100 g of the powder body and 20 g of polyetheretherketone resin are evenly dispersed to obtain the mixed powder.

[0079] The powder body is prepared by the following method: 78 g of natural flake graphite (35 μm), 2 g of short-cut carbon fiber (length 0.5 mm, diameter 5 μm) and 20 g of copper powder (20 μm) are uniformly mixed to obtain the powder body.

[0080] The mixing is carried out in a mixing device; the mixing speed is 800 rpm, and the mixing time is 30 min.

[0081] The dispersing rotation speed is 800 rpm, and the dispersing time is 60 min. During the dispersing period, the temperatures of the powder body and the resin are both less than 50°C.

[0082] In step S02,

[0083] The first solution is a 5 g / L sodium hydroxide solution.

[0084] The soaking time is 15 minutes.

[0085] The cleaning is performed by washing with deionized water.

[0086] The second solution is a mixed solution containing phosphoric acid and chromic acid, the concentration of the phosphoric acid is 220 g / L, and the concentration of the chromic acid is 150 g / L.

[0087] The water washing is performed by using deionized water.

[0088] In step S03,

[0089] The third solution is a mixed solution of stannous chloride and hydrochloric acid; the concentration of the stannous chloride is 15 g / L, the amount of hydrochloric acid added is 36 ml / L, and the hydrochloric acid is 37% by mass (12 mol / L).

[0090] The soaking temperature is 25° C. and the soaking time is 10 min.

[0091] The activation solution is a mixed solution of palladium chloride and hydrochloric acid; the concentration of the palladium chloride is 0.5 g / L, and the concentration of the hydrochloric acid is 30 ml / L.

[0092] The activation time is 5 min.

[0093] In step S04,

[0094] The plating solution contains 20 g / L nickel sulfate, 20 g / L sodium hypophosphite, 10 g / L sodium acetate and 10 g / L sodium citrate.

[0095] The pH value of the plating solution is 4.5, and the pH value is adjusted by acetic acid or sodium hydroxide. The temperature of the plating solution is 80°C.

[0096] The metal plating treatment is carried out during stirring; the stirring speed is 100 rpm; and the metal plating treatment time is 50 min.

[0097] The washing is done by washing with deionized water. The drying temperature is 120°C.

[0098] The prepared fuel cell graphite metal composite bipolar plate has a low contact resistance (3.5mΩ·cm 2 About), high molding efficiency and good performance.

[0099] Example 2

[0100] A method for preparing a fuel cell graphite metal composite bipolar plate comprises the following steps:

[0101] S01, heating and pressurizing the mixed powder to obtain a formed composite plate; the heating temperature is 370° C.; the pressurizing pressure is 25 MPa, and the pressurizing time is 15 min;

[0102] S02, soaking the formed composite plate in a first solution at 70° C., taking it out, and washing it to neutrality to obtain a pretreated composite plate; soaking the pretreated composite plate in a second solution at 75° C., taking it out, and washing it with water to obtain a treated composite plate;

[0103] S03, soaking the treated composite plate in a third solution, taking it out, washing it with water, and then placing it in an activation solution for activation, washing it with water, to obtain an activated plate;

[0104] S04, placing the activated electrode plate in a plating solution for metal plating, then washing with water, and drying to obtain a fuel cell graphite metal composite bipolar plate (graphite metal composite electrode plate with metal plated on the surface).

[0105] In step S01,

[0106] The mixed powder is prepared by the following method: 100 g of the powder body and 20 g of polyetheretherketone resin are evenly dispersed to obtain the mixed powder.

[0107] The powder body is prepared by the following method: 70 g of natural flake graphite (35 μm), 2 g of short-cut carbon fiber (length 0.5 mm, diameter 5 μm) and 28 g of copper powder (20 μm) are uniformly mixed to obtain the powder body.

[0108] The mixing is carried out in a mixing device; the mixing speed is 800 rpm, and the mixing time is 30 min.

[0109] The dispersing rotation speed is 800 rpm, and the dispersing time is 60 min. During the dispersing period, the temperatures of the powder body and the resin are both less than 50°C.

[0110] In step S02,

[0111] The first solution is a 5 g / L sodium hydroxide solution.

[0112] The soaking time is 15 minutes.

[0113] The cleaning is performed by washing with deionized water.

[0114] The second solution is a mixed solution containing phosphoric acid and chromic acid, the concentration of the phosphoric acid is 220 g / L, and the concentration of the chromic acid is 150 g / L.

[0115] The water washing is performed by using deionized water.

[0116] In step S03,

[0117] The third solution is a mixed solution of stannous chloride and concentrated hydrochloric acid; the concentration of the stannous chloride is 15 g / L, the amount of concentrated hydrochloric acid added is 36 ml / L, and the concentration of the concentrated hydrochloric acid is 37% (12 mol / L).

[0118] The soaking temperature is 25° C. and the soaking time is 10 min.

[0119] The activation solution is a mixed solution of palladium chloride and hydrochloric acid; the concentration of the palladium chloride is 0.5 g / L, and the concentration of the hydrochloric acid is 30 ml / L.

[0120] The activation time is 5 min.

[0121] In step S04,

[0122] The plating solution contains 20 g / L nickel sulfate, 20 g / L sodium hypophosphite, 10 g / L sodium acetate and 10 g / L sodium citrate.

[0123] The pH value of the plating solution is 4.5, and the pH value is adjusted by acetic acid or sodium hydroxide. The temperature of the plating solution is 80°C.

[0124] The metal plating treatment is carried out during stirring; the stirring speed is 100 rpm; and the metal plating treatment time is 50 min.

[0125] The washing is done by washing with deionized water. The drying temperature is 120°C.

[0126] The prepared fuel cell graphite metal composite bipolar plate has a low contact resistance (3.5mΩ·cm 2 About), high molding efficiency and good performance.

[0127] Example 3

[0128] A method for preparing a fuel cell graphite metal composite bipolar plate comprises the following steps:

[0129] S01, heating and pressurizing the mixed powder to obtain a formed composite plate; the heating temperature is 280° C.; the pressurizing pressure is 25 MPa, and the pressurizing time is 15 min;

[0130] S02, soaking the formed composite plate in a first solution at 70° C., taking it out, and washing it to neutrality to obtain a pretreated composite plate; soaking the pretreated composite plate in a second solution at 75° C., taking it out, and washing it with water to obtain a treated composite plate;

[0131] S03, soaking the treated composite plate in a third solution, taking it out, washing it with water, and then placing it in an activation solution for activation, washing it with water, to obtain an activated plate;

[0132] S04, placing the activated electrode plate in a plating solution for metal plating, then washing with water, and drying to obtain a fuel cell graphite metal composite bipolar plate (graphite metal composite electrode plate with metal plated on the surface).

[0133] In step S01,

[0134] The mixed powder is prepared by the following method: 100 g of the powder body and 20 g of polystyrene resin are evenly dispersed to obtain the mixed powder.

[0135] The powder body is prepared by the following method: 78 g of natural flake graphite (35 μm), 2 g of chopped carbon fiber (length 0.5 mm, diameter 5 μm) and 20 g of stainless steel powder (30 μm) are uniformly mixed to obtain the powder body.

[0136] The mixing is carried out in a mixing device; the mixing speed is 800 rpm, and the mixing time is 30 min.

[0137] The dispersing rotation speed is 800 rpm, and the dispersing time is 60 min. During the dispersing period, the temperatures of the powder body and the resin are both less than 50°C.

[0138] In step S02,

[0139] The first solution is a 5 g / L sodium hydroxide solution.

[0140] The soaking time is 15 minutes.

[0141] The cleaning is performed by washing with deionized water.

[0142] The second solution is a mixed solution containing phosphoric acid and chromic acid, the concentration of the phosphoric acid is 220 g / L, and the concentration of the chromic acid is 150 g / L.

[0143] The water washing is performed by using deionized water.

[0144] In step S03,

[0145] The third solution is a mixed solution of stannous chloride and hydrochloric acid; the concentration of the stannous chloride is 15 g / L, the amount of hydrochloric acid added is 36 ml / L, and the hydrochloric acid is 37% by mass (12 mol / L).

[0146] The soaking temperature is 25° C. and the soaking time is 10 min.

[0147] The activation solution is a mixed solution of palladium chloride and hydrochloric acid; the concentration of the palladium chloride is 0.5 g / L, and the concentration of the hydrochloric acid is 30 ml / L.

[0148] The activation time is 5 min.

[0149] In step S04,

[0150] The plating solution contains 20 g / L nickel sulfate, 20 g / L sodium hypophosphite, 10 g / L sodium acetate and 10 g / L sodium citrate.

[0151] The pH value of the plating solution is 4.5, and the pH value is adjusted by acetic acid or sodium hydroxide. The temperature of the plating solution is 80°C.

[0152] The metal plating treatment is carried out during stirring; the stirring speed is 100 rpm; and the metal plating treatment time is 50 min.

[0153] The water washing is cleaned by deionized water. The drying temperature is 120°C. The prepared fuel cell graphite metal composite bipolar plate has a low contact resistance (3.5mΩ·cm 2 About), high molding efficiency and good performance.

[0154] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a fuel cell graphite metal composite bipolar plate, characterized in that: The steps include: S01, heating and pressurizing the mixed powder to obtain a formed composite plate; the heating temperature is 280°C to 400°C; the pressurizing pressure is 15MPa to 25MPa, and the pressurizing time is 10min to 20min; S02, soaking the formed composite electrode plate in the first solution at 60° C. to 70° C., taking it out, and washing it to neutrality to obtain a pretreated composite electrode plate; At 70° C. to 80° C., soaking the pretreated composite electrode plate in a second solution, taking it out, and washing it with water to obtain a treated composite electrode plate; S03, soaking the treated composite plate in a third solution, taking it out, washing it with water, and then placing it in an activation solution for activation, washing it with water, to obtain an activated plate; S04, placing the activated electrode plate in a plating solution for metal plating, then washing and drying to obtain a fuel cell graphite metal composite bipolar plate.

2. The method for preparing a fuel cell graphite metal composite bipolar plate according to claim 1, characterized in that: In step S01, the mixed powder is prepared by the following method: a powder body and a resin are evenly dispersed to obtain a mixed powder; a mass ratio of the resin to the powder body is 1:4 to 1:

6.

3. The method for preparing a fuel cell graphite metal composite bipolar plate according to claim 2, characterized in that: The powder body is prepared by the following method: taking the mass of the powder body as 100%, 60% to 80% of graphite powder, 0.5% to 5% of carbon fiber and 20% to 40% of metal powder are uniformly mixed to obtain the powder body.

4. The method for preparing a fuel cell graphite metal composite bipolar plate according to claim 3, characterized in that: The graphite powder is natural graphite powder, artificial graphite powder or flexible graphite powder; The metal powder is one of stainless steel powder, titanium powder, aluminum powder or copper powder.

5. The method for preparing a fuel cell graphite metal composite bipolar plate according to claim 4, characterized in that: The particle size of the natural graphite powder is 10 μm to 50 μm; the particle size of the artificial graphite powder is 15 μm to 45 μm; the particle size of the flexible graphite powder is 20 μm to 40 μm; The carbon fiber has a length of 0.1 mm to 10 mm and a diameter of 5 μm to 10 μm; The particle size of the stainless steel powder is 25 μm to 75 μm; the particle size of the titanium powder is 30 μm to 90 μm; the particle size of the aluminum powder is 15 μm to 60 μm; the particle size of the copper powder is 10 μm to 50 μm; The mixing is carried out in a mixing device; the mixing rotation speed is 600 rpm to 800 rpm, and the mixing time is 30 min to 40 min.

6. The method for preparing a fuel cell graphite metal composite bipolar plate according to claim 2, characterized in that: The resin is a thermoplastic resin; The dispersing rotation speed is 600 rpm to 800 rpm, and the dispersing time is 40 min to 60 min. During the dispersing period, the temperatures of the powder body and the resin are both less than 50°C.

7. The method for preparing a fuel cell graphite metal composite bipolar plate according to claim 1, characterized in that: In step S02, The first solution is a 5 g / L to 10 g / L sodium hydroxide solution; The soaking time is 10 to 15 minutes; The second solution is a mixed solution containing phosphoric acid and chromic acid, the concentration of the phosphoric acid is 200 g / L to 300 g / L, and the concentration of the chromic acid is 100 g / L to 200 g / L.

8. The method for preparing a fuel cell graphite metal composite bipolar plate according to claim 1, characterized in that: In step S03, The third solution is a mixed solution of stannous chloride and hydrochloric acid; the concentration of the stannous chloride is 15g / L to 20g / L, the amount of hydrochloric acid added is 30 to 40ml / L, and the hydrochloric acid is 37% by mass; The soaking temperature is 25°C; the soaking time is 8 to 10 minutes; The activation solution is a mixed solution of palladium chloride and hydrochloric acid; the concentration of the palladium chloride is 0.3g / L to 0.5g / L, and the concentration of the hydrochloric acid is 20ml / L to 30ml / L; The activation time is 3 min to 5 min.

9. The method for preparing a fuel cell graphite metal composite bipolar plate according to claim 1, characterized in that: In step S04, The plating solution contains 20g / L to 30g / L nickel sulfate, 20g / L to 30g / L sodium hypophosphite, 10g / L to 15g / L sodium acetate and 10g / L to 15g / L sodium citrate; The pH value of the plating solution is 4.5-5.0; the temperature of the plating solution is 80° C.-90° C.; The metal plating process is carried out during stirring; the stirring speed is 80 rpm to 100 rpm; the metal plating process lasts for 40 min to 60 min; The drying temperature is 100°C to 120°C.

10. A fuel cell graphite metal composite bipolar plate, characterized in that: The fuel cell graphite metal composite bipolar plate is prepared by the preparation method described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Conductive composite material and preparation method thereof, and fuel cell stack bipolar plate

    CN113621235A

  • Low-contact-resistance and high-gas-barrier composite graphite bipolar plate and preparation method thereof

    CN117691142A

  • Separator for solid polymer fuel cell and its manufacturing method

    JP2006004853A